Comparative Analysis of Profitability Before and After The Covid 19 Pandemic at PT. Kimia FarmaTbk. - Indrayani Indrayani (ProBisnis : Jurnal Manajemen, 2023)
This study uses a comparative descriptive research method which aims to determine differences in the profitability ratios of Return On Assets (ROA) and Return On Equity before and after the Covid-19 pandemic at a pharmaceutical company, namely PT. Kimia Farma Tbk. PT. Kimia Farma Tbk. obtained by accessing the official website of the Indonesia Stock Exchange, namely www.idx.co.id. Based on the results of the analysis carried out, it can be concluded that the Covid 19 pandemic had an impact on the health of PT. Kimia Farma Tbk, which is based on the ROA value obtained in 2018 before the pandemic the company was in Very Healthy condition, during the 2019 and 2020 pandemic the company was in Unhealthy condition, in 2021 the company was in Healthy condition, and in 2022 the company will return to Unhealthy conditions. Meanwhile, based on the ROE value obtained in 2018 PT. Kimia Farma Tbk. in a Healthy condition, during the 2019 – 2020 pandemic and it will still have an impact in 2021 the company is in an Unsound condition, and will experience a decline where in 2022 the company's condition is categorized as Unsound.